2020
DOI: 10.1177/0363546520962071
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Comparison of 2 Hip Capsular Reconstruction Techniques: Iliotibial Band Autograft Versus Achilles Tendon Allograft

Abstract: Background: Several techniques for hip capsular reconstruction have been described to address gross instability or microinstability due to capsular deficiency. However, objective biomechanical data to support their use are lacking. Purpose: To compare the kinematic effect of 2 capsular reconstruction techniques (iliotibial band [ITB] graft and Achilles tendon graft). Kinematic effect encompassed rotational range of motion (ROM) as well as joint translation in the coronal, sagittal, and axial planes. Study Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…investigated eight paired, cadaveric pelvises and recorded rotational ROM and joint translation in the coronal, sagittal and axial planes while applying internal–external rotation and abduction–adduction rotation torques at different degrees of flexion [ 33 ]. Pairs were randomly allocated to either ITB or Achilles reconstruction and were compared to intact and capsulectomy conditions [ 33 ]. Philippon et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…investigated eight paired, cadaveric pelvises and recorded rotational ROM and joint translation in the coronal, sagittal and axial planes while applying internal–external rotation and abduction–adduction rotation torques at different degrees of flexion [ 33 ]. Pairs were randomly allocated to either ITB or Achilles reconstruction and were compared to intact and capsulectomy conditions [ 33 ]. Philippon et al .…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Pasic et al . showed that at 90° of hip flexion, both reconstruction techniques utilizing ITB and Achilles tendon had significantly lower degrees of total rotation than the capsulectomy state with values similar to the intact state [ 33 ]. Increased coronal plane stability in the hip was also observed with capsular reconstruction, especially with the Achilles tendon allograft [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a biomechanical study of 8 paired hemi-pelvises (16 hips), Pasic et al. 13 evaluated the hip joint range of motion in the intact state, after capsulectomy, and in the reconstructed state. Pairs were randomly allocated to either iliotibial band or Achilles reconstruction groups.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found no difference in range of motion based on graft type. 13 Although early results of our capsular reconstruction technique have been promising in our clinical practice, studies reporting medium- to long-term patient-reported outcomes and biomechanical studies are necessary to support capsular reconstruction without the use of a graft. Given our encouraging early results, we will continue to perform anchor-based reconstruction without allograft augmentation in select patients with capsular deficiency in those who have adequate femoral sided capsular tissue for complete, watertight closure.…”
Section: Discussionmentioning
confidence: 99%